2015
DOI: 10.3102/0034654314551065
|View full text |Cite
|
Sign up to set email alerts
|

Having Their Lives Narrowed Down? The State of Black Women’s College Success

Abstract: Contradictory trends emerge relative to Black women's college success: They have doubled their enrollment rates in thirty years but their graduation rates remain behind those of White and Asian women. This integrative, interdisciplinary review of both student-and institutional-level factors explores the role of individual characteristics and backgrounds, relationships, and institutional support structures relative to Black women's success in college. The findings reveal that African American women's lives may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 121 publications
(252 reference statements)
3
79
0
Order By: Relevance
“…Social support from peers and participation in student activities and organizations have been shown to be strong predictors of academic success among African American students (Guiffrida, 2003;Harper & Quaye, 2007;Winkle-Wagner, 2015). Hurtado, Carter, and Spuler (1996) found that peer support was predictive of college outcomes for Latino/a students.…”
Section: Peer Supportmentioning
confidence: 99%
“…Social support from peers and participation in student activities and organizations have been shown to be strong predictors of academic success among African American students (Guiffrida, 2003;Harper & Quaye, 2007;Winkle-Wagner, 2015). Hurtado, Carter, and Spuler (1996) found that peer support was predictive of college outcomes for Latino/a students.…”
Section: Peer Supportmentioning
confidence: 99%
“…While Black women possess a range of experience within the system of higher education, institutions have built support systems within this community to help Black women thrive. An intentional effort on the part of institutions to make space and understand the role and impact of Black women in higher education is necessary for retention (Hannon, Woodside, Pollard, & Roman, 2016;Patton & McClure, 2009;Porter & Dean, 2015;Winkle-Wagner, 2015). In their qualitative study Porter and Dean (2015) employed a phenomenological approach to identify factors that influence the identity development and meaning making of four Black undergraduate women at a PWI.…”
Section: Black College Women's Experiencesmentioning
confidence: 99%
“…This is indicative of Black women continually resisting oppressive structures of higher education. The symbolism of resistance in the "Freedom" performance is reflected in the literature on Black collegiate women's experiences, which emphasizes the determinism and motivation pulled from within during challenging times throughout the educational journey (Everett, 2015;Patton & McClure, 2009;Winkle-Wagner, 2015). In an effort to combat negative racial stereotypes some Black women have exhibited "prove-them-wrong-syndrome" which is "a response of determination and dedication to a task or goal that African American students use to overcome adversity and combat stereotypes" (Shavers & Moore, 2014, p. 26).…”
Section: Resisting the Oppressive Structures Of Higher Education And mentioning
confidence: 99%
See 1 more Smart Citation
“…These meta-analyses typically report effect sizes (signified by d ), which refer to the difference between the ITS condition and a control condition, calibrated in standard deviation units. The reported meta-analyses show positive effect sizes that vary from d = 0.05 (Dynarsky et al 2007; Steenbergen-Hu and Cooper 2014) to d = 1.08 (Dodds and Fletcher 2004), but most hover between d = 0.40 and d = 0.80 (Kulik and Fletcher 2015; Ma et al 2014; Steenbergen-Hu and Cooper 2013; VanLehn 2011). A reasonable meta-meta estimate from all of these meta-analyses is d = 0.60.…”
Section: Introductionmentioning
confidence: 99%